Feminisme dan Teologi: Perubahan Paradigma Dalam Pendidikan Agama Kristen - Oktavianus Rangga; Nelcy Mbelanggedo (SOPHIA: Jurnal Teologi dan Pendidikan Kristen, 2025)
In Christian Religious Education (CRE), the relationship between feminism and theology has triggered a significant paradigm shift, particularly in reexamining the structure of knowledge that has been shaped by a patriarchal perspective. Through a critical hermeneutic approach and literature review, this study reveals how feminist theology challenges gender bias in biblical interpretation and opens up space for women's experiences as legitimate epistemological sources. This transformation has implications for the reconstruction of a more gender-responsive CRE curriculum, including the use of inclusive language, representation of female biblical figures, and dialogic learning strategies that foster critical awareness. However, the integration of a feminist perspective into religious pedagogy positions students as active subjects in the process of just and equal faith formation. The results of this study confirm that the renewal of CRE is not limited to the addition of gender issues, but rather a profound theological-pedagogical reconstruction to build an education that is more inclusive, liberating, and aligned with the values ​​of equality and human dignity in the Christian faith.Dalam Pendidikan Agama Kristen (PAK), relasi antara feminisme dan teologi telah memicu perubahan paradigma yang signifikan, terutama dalam meninjau ulang struktur pengetahuan yang selama ini dibentuk oleh perspektif patriarkal. Melalui pendekatan hermeneutika kritis dan studi pustaka, kajian ini mengungkap bagaimana teologi feminis menantang bias gender dalam penafsiran Alkitab serta membuka ruang bagi pengalaman perempuan sebagai sumber epistemologis yang sah. Transformasi ini berimplikasi pada rekonstruksi kurikulum PAK yang lebih responsif gender, mencakup penggunaan bahasa inklusif, representasi tokoh perempuan Alkitab, dan strategi pembelajaran dialogis yang mendorong kesadaran kritis. Namun, integrasi perspektif feminis dalam pedagogi agama menempatkan peserta didik sebagai subjek aktif dalam proses pembentukan iman yang adil dan setara. Hasil kajian ini menegaskan bahwa pembaruan PAK tidak sebatas penambahan isu gender, tetapi merupakan rekonstruksi teologis-pedagogis yang mendalam demi membangun pendidikan yang lebih inklusif, membebaskan, dan selaras dengan nilai kesetaraan serta martabat manusia dalam iman Kristen.